Dielectric Nanorod Scattering and its Influence on Material Interfaces - Gauri M. Mangalgiri (Nature Portfolio, 2017)
Abstract This work elaborates on the high scattering which dielectric nanorods exhibit and how it can be exploited to control light propagation across material interfaces. A detailed overview of how dielectric nanorods interact with light through a combination of dipolar scattering and leaky modes is performed via outward power flux calculations. We establish and account for design parameters that best result in light magnification owing to resonant behavior of nanorods. Impact of material parameters on scattering and their dispersion have been calculated to establish that low loss dielectric oxides like ZnO when nanostructured show excellent antenna like resonances which can be used to control light coupling and propagation. Interfacial scattering calculations demonstrate the high forward directivity of nanorods for various dielectric interfaces. A systematic analysis for different configurations of single and periodic nanorods on air dielectric interface emphasizes the light coupling tendencies exhibited by nanorods to and from a dielectric. Spatial characteristics of the localized field enhancement of the nanorod array on an air dielectric interface show focusing attributes of the nanorod array. We give a detailed account to tailor and selectively increase light propagation across an interface with good spectral and spatial control.